THE EFFECT OF FINANCIAL ATTITUDE, FINANCIAL KNOWLEDGE, AND LOCUS OF CONTROL ON FINANCIAL MANAGEMENT BEHAVIOR (Study On Students of Management Departement, Faculty of Economics and Business, Malikussaleh University) - Ristati; Alisa Adelena; Marzuki; Muttaqien (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
This study aims to determine how the influence of financial attitude, financial knowledge, and locus of control on financial management behavior in students of the Department of Management, Faculty of Economics and Business, Malikussaleh University. The data used in this study is primary data obtained by distributing questionnaires to 94 students of the Department of Management, Faculty of Economics and Business, Malikussaleh University who were used as samples in this study. The data analysis technique used is multiple linear regression analysis using the help of SPSS software version 26. The results showed that financial attitude, financial knowledge, and locus of control had a positive and significant effect on financial management behavior in students of the Department of Management, Faculty of Economics and Business, Malikussaleh University.